The Alignment of Folklore and Literature Learning in Schools Against Students' Eco-literacy Competencies - Youpika, Fitra; Sumiyadi; Permadi, Tedi; Sunendar, Dadang; Yandryati, Jenny (UNIB Press, 2024)
This research is about local literature (folklore) and eco-literacy. It was conducted to find information of the alignment between folklore, literature learning in schools, and students' eco-literacy. This research used descriptive-qualitative research design. The data used for this research is in the form of answers from respondents about written questions that have been distributed online. Total respondents were 89 students from 5 schools (junior and senior high schools) in Bengkulu. Data analysis was conducted through data reduction, presentation (description), and conclusion. The findings of this study are, first, Junior and Senior High School students in Bengkulu like folklores from their district. Most of these students like legend’s type folklore compared to other type stories. Currently, folklores can still be found in the community, although it is not easy because the spoke person are old and many have died. The content of Bengkulu folklores has values or teachings about nature and ecosystem conservation. Second, local literature is taught in junior and senior high schools in Bengkulu. Students enjoy learning literature, especially local literature. The last, the level of environmental literacy among students is still relatively low. This can be seen by the lack of students' attention for waste and environmental conservation. In this regard, learning literature and folklore in schools is in line with students' eco-literacy competencies. However, this has not been implemented optimally, so it is hoped that local literature (folklore) can give contribution in nature and ecosystem conservations by increasing the eco-literacy of students and society.